Les assurances de personnes – rétrospective et perspective - Bousquet, Jean-Maurice (Assurances, 1985)
The main purpose of Mr. Bousquet's article is to review the life insurance sector in the light of the new Bill 75 passed by Quebec Government on June 20, 1984 which removes some of the barriers between financial institutions. This article also deals with the position of ACCAP about the new legislation and the control of intermediaries based on better organized and refined classifications.